TREATMENT OUTCOMES OF PATIENTS WITH HAIRY CELL LEUKAEMIA; A 16-YEAR EXPERIENCE AT A TERTIARY CARE CENTER IN PAKISTAN - Muhammad Yousaf; Ali Khan, Mehreen; Iftikhar, Raheel; Chaudary, Qamar Un Nisa; Shahbaz, Nighat; Ahmad, Uzair; Javed, Hammad (Journal of Ayub Medical College Abbottabad, 2022)
Background: Hairy cell leukaemia (HCL) is an uncommon neoplasm of mature B-lymphoid cells which is characterized by cytopenias, commonly of all three cell lines, with typical hairy cells on peripheral smear and/or bone marrow along with organomegaly. Objective was to document the outcomes of HCL patients treated at a tertiary care hospital in Pakistan. Methods: Medical records of patients from 2004 to 2020 were reviewed and data was collected to assess patient’s demographics, symptomatology, remission rate and overall survival. The record flies of all patients presenting to AFBMTC with HCL were included in the study. The record file with insufficient data were excluded Results: 26 patients with a mean age of 48.12±11.43 years were diagnosed with HCL and treated at AFBMTC. Out of these, 23 (88.4%) were male and 03 (11.5%) females. The main presenting complaints were generalized body aches (34.6%), fever (15.4%), incidental finding of cytopenias (11.5%) and abdominal discomfort (26.9%). Splenomegaly was found in 76.92% while hepatomegaly was found in 46.15% of patients. A total of 12 (46.15%) patients received Cladribine (either intravenous or subcutaneous) and splenectomy was done in 7 (26.92%) as 1st line treatment. Eleven patients out of 12 (83.33%) who received Cladribine and 05 (71.42%) patients out of seven who underwent splenectomy; achieved complete remission (CR) after 1st line of treatment. One patient received Cladribine as 1st line of treatment but did not respond and CHOP regimen was given as second line. Out of the 26 patients, 5 patients (19.23%) relapsed at a median interval of 5.83±6.6 years. Two patients received Cladribine + Rituximab while 03 patients received cladribine as their salvage therapy. Disease free survival (DFS) of 71.4% among the patients underwent splenectomy while 75.0% among the patients received Cladribine. DFS for combination therapy (included CHOP and CVP) was 66.7% while OS was calculated among patients who received cladribine, splenectomy and combination chemotherapy as 100%, 85.7%, 66.7% respectively. Conclusion: Cladribine has a significant efficacy and encouraging acute and long-term benefits when administered to patients with HCL. A single course of cladribine was able to induce CR in a vast majority of patients. At a median follow up of 4.6 years the OS was 100% with cladribine and 85% with splenectomy. Those who relapsed were successfully retreated with cladribine + Rituximab.